Upaya Strategis Peningkatan Mutu Pendidikan di Madrasah Ibtidaiyah: Pendekatan Studi Kasus Holistik - Abidin, Miftahul; Zainuri, Ahmad; Yasir, Muslim Gani; Ahmad, Ahmad (Universitas Islam Negeri Raden Fatah Palembang, 2025)
This study explores strategic efforts to improve the quality of education at Madrasah Ibtidaiyah (MI) Hijriyah 2 Palembang through a holistic approach. The research employs a qualitative case study method to analyze various dimensions of educational development, including curriculum enhancement, teacher professional development, infrastructure improvement, technology integration, and stakeholder involvement. Data were collected through interviews, observations, documentation, and questionnaires involving school leaders, teachers, students, and parents. The findings reveal that MI Hijriyah 2 has successfully implemented integrated strategies that contribute to students' academic achievement, character formation, and religious values. Despite facing several challenges such as limited resources and technological infrastructure, the school demonstrates resilience through collaborative planning and continuous evaluation. The study concludes with recommendations to strengthen teacher training, community engagement, and policy support to sustain educational quality in Islamic primary schools.